Case report: Rare case of a preoperatively diagnosed spermatic cord paraganglioma and literature review - Hao, Yining; Li, Xiuci; Xie, Jing; He, Wei; Wang, Chenghe; Sun, Fukang (Frontiers in Oncology, 2024)
Paraganglioma (PGL) is rare, and PGL that arises from the urogenital system is even rarer. Here we report a case of PGL in spermatic cord and review the relevant literatures. We encountered a 15-year-old boy with a history of hypertension for almost 2 years, accompanied with headache and palpitations. His serum and urine catecholamines were elevated, but no adrenal lesions were detected, suggesting the existence of PGL. Upon physical examination, a painless nodule adherent to the spermatic cord in the right scrotum was found. A systemic Ga68 DOTATATE PET-CT was then performed, and it revealed a mass with high DOTATATE uptake in the right scrotum. The CT, MRI, and ultrasound images showed the abundant blood supply to the tumor. Based on the above-mentioned imaging and biochemical information, a diagnosis of PGL was made prior to surgery. After 2 weeks of preparation with Cardura, an open surgery was performed to remove the tumor together with the right testis and right epididymis. The blood pressure increased to 180/100 mmHg when the tumor was touched intraoperatively and decreased to 90/55 mmHg after the tumor was removed. Post-operative pathology confirmed our diagnosis of PGL originating from the spermatic cord. Immunohistochemical (IHC) staining showed SDHB (+), CgA (+), synaptophysin (+), GATA3 (+), CD56 (+), sertoli cells S-100 (+), and Ki67 (5%). Genetic testing revealed a missense mutation in the SDHA gene. Only 16 cases of spermatic cord PGL have been reported to date. Although it is easy to diagnose by histology and IHC examinations, preoperative diagnosis is quite important as it can actually reduce intraoperative complications.